Expression of the Escherichia coli K5 capsular antigen: immunoelectron microscopic and biochemical studies with recombinant E. coli. - Kröncke, K D (1990)
The capsular K5 polysaccharide, a representative of group II capsular antigens of Escherichia coli, has been cloned previously, and three gene regions responsible for polymerization and surface expression have been defined (I. S. Roberts, R. Mountford, R. Hodge, K. B. Jann, and G. J. Boulnois, J. Bacteriol. 170:1305-1310, 1988). In this report, we describe the immunoelectron microscopic analysis of recombinant bacteria expressing the K5 antigen and of mutants defective in either region 1 or region 3 gene functions, as well as the biochemical analysis of the K5 capsular polysaccharide. Whereas the K5 clone expressed the K5 polysaccharide as a well-developed capsule in about 25% of its population, no capsule was observed in whole mount preparations and ultrathin sections of the expression mutants. Immunogold labeling of sections from the region 3 mutant revealed the capsular K5 polysaccharide in the cytoplasm. With the region 1 mutant, the capsular polysaccharide appeared associated with the cell membrane, and, unlike the region 3 mutant polysaccharide, the capsular polysaccharide could be detected in the periplasm after plasmolysis of the bacteria. Polysaccharides were isolated from the homogenized mutants with cetyltrimethylammonium bromide. The polysaccharide from the region 1 mutant had the same size as that isolated from the capsule of the original K5 clone, and both polysaccharides were substituted with phosphatidic acid. The polysaccharide from the region 3 mutant was smaller and was not substituted with phosphatidic acid. These results prompt us to postulate that gene region 3 products are involved in the translocation of the capsular polysaccharide across the cytoplasmic membrane and that region 1 directs the transport of the lipid-substituted capsular polysaccharide through the periplasm and across the outer membrane.